2020
DOI: 10.3390/foods9081092
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Water Activity on the Inactivation and Gene Expression of Listeria monocytogenes during Refrigerated Storage of Pressurized Dry-Cured Ham

Abstract: Listeria monocytogenes population and the expression patterns of three virulence (plcA, hly, and iap) and one stress-related (sigB) genes in dry-cured ham with different water activity (aw) values (0.92, 0.88, and 0.84) and treated with high pressure processing (HPP, 450 MPa/10 min and 600 MPa/5 min) were monitored throughout 30 days (d) at 4 °C. The antimicrobial effect of HPP at 600 MPa against L. monocytogenes S4-2 (serotype 1/2b) and S12-1 (serotype 1/2c) was greater in dry-cured ham with aw values of 0.92… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Gene expression pro ling of the response of L. monocytogenes to HPP has previously been studied by RNA-seq [12], microarray [31,32], and qPCR [33]. For example, it has been shown that a mutation in ctsR causes barotolerance and a ctsR deletion mutant of L. monocytogenes shows increased expression of Clp protease and PTS system genes after HPP [31].…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression pro ling of the response of L. monocytogenes to HPP has previously been studied by RNA-seq [12], microarray [31,32], and qPCR [33]. For example, it has been shown that a mutation in ctsR causes barotolerance and a ctsR deletion mutant of L. monocytogenes shows increased expression of Clp protease and PTS system genes after HPP [31].…”
Section: Introductionmentioning
confidence: 99%
“…Heat treatment is one of the traditional microbial control methods in agricultural and food processing applications. There are many factors influencing microbial inactivation, such as temperature, water activity (a w ), heating rate and physical structure of food matrices [ 11 , 12 , 13 , 14 , 15 , 16 ]. Decimal reduction time ( D -value), the time (min) required to reduce the microbial population by 10-fold (1 log) at a constant temperature (°C), is used to measure microbial heat resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal inactivation kinetic study of microorganisms can provide solid and reliable thermal processing parameters (heating temperature and time) for the food industry. The linear model described by first-order kinetics is widely used to determine the D -value for microorganisms, which can accurately predict the linear microbial inactivation curve [ 16 , 22 , 23 ]. In addition, the Weibull model has been successfully applied to better fit nonlinear microbial inactivation curves [ 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The surface and interior of HHP-treated ham (applied for 10 min at 450 MPa or 5 min at 600 MPa) depicted a 2 and 3 log units reduction in L. monocytogenes populations, respectively, despite the varying levels of water activity [ 66 ]. However, authors observed that the effectiveness of HHP treatments (at 600 MPa for 5 min) against L. monocytogenes was influenced by the physicochemical properties of the food matrix, such as lower water activity, which diminished the antimicrobial impact of HHP.…”
Section: Nonthermal Decontamination Technologiesmentioning
confidence: 99%